Production of recombinant barley xylanase inhibitor in Pichia pastoris and its inhibitory effect on premature yeast flocculation. Issue 2 (28th March 2022) - Shang, Yueling; Li, Xiaomin; Cai, Guolin; Wang, Dujun; Li, Fengwei; Lu, Jian; Yu, Xiaohong
Abstract : The xylanase inhibitor from barley ( Hordeum vulgare L.) can inhibit diverse microbial endoxylanases, which have been proposed to induce premature yeast flocculation (PYF) during fermentation with microbially contaminated barley malt. To investigate the inhibition of PYF by recombinant Hordeum vulgare L. xylanase inhibitor (rHVXI), it was constitutively and inducibly expressed in Pichia pastoris using the glyceraldehydes‐3‐phosphate dehydrogenase ( GAP ) promoter and the methanol‐induced alcohol oxidase ( AOX 1) promoter, resulting in strains GAP/S and AOX1/αS. With the GAP promoter, the transformants exhibited inhibition against xylanase, with the GAP/S‐11 strain showing the greatest activity of rHVXI from 20 transformants. The rHVXI inhibitor was purified and added during the mashing process of PYF positive (PYF+) malt to evaluate its inhibitory effect on PYF. The rHVXI inhibitor affected yeast flocculation during fermentation of PYF+ wort, demonstrating its application to mitigate PYF factors. © 2022 The Institute of Brewing & Distilling